2010
DOI: 10.1007/s12558-010-0059-3
|View full text |Cite
|
Sign up to set email alerts
|

Aspects épidémiologiques et histopathologiques des affections mammaires à Ouagadougou

Abstract: Notre travail a porté sur 992 cas d'affections mammaires colligés, de janvier 2001 à décembre 2006, dans les laboratoires d'anatomie pathologique de la ville de Ouagadougou. L'objectif a été de déterminer les aspects épi-démiologiques et histologiques des affections mammaires dans la ville de Ouagadougou. Il est ressorti de cette étude que : 1) les cas d'affections mammaires diagnostiqués ont augmenté avec le temps ; 2) les trois quarts des lésions diagnostiquées ont été bénignes ; 3) l'âge moyen des patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 1 publication
2
6
0
Order By: Relevance
“…This average age is slightly higher than that reported in African literature for young women. Darre et al in 2017 in Togo, Bonane-Thieba et al in 2010 in Burkina-Faso, Bouzid et al in 2013 in Tunisia, and Gueye et al in 2016 in Senegal had respectively found an average age of 32.6 years, 31, 3 years, 30.9 years and 29.7 years [4][5][6][7][8]. The average age of cancer in young women in Cotonou is comparable to data from Western authors.…”
Section: Agementioning
confidence: 54%
See 3 more Smart Citations
“…This average age is slightly higher than that reported in African literature for young women. Darre et al in 2017 in Togo, Bonane-Thieba et al in 2010 in Burkina-Faso, Bouzid et al in 2013 in Tunisia, and Gueye et al in 2016 in Senegal had respectively found an average age of 32.6 years, 31, 3 years, 30.9 years and 29.7 years [4][5][6][7][8]. The average age of cancer in young women in Cotonou is comparable to data from Western authors.…”
Section: Agementioning
confidence: 54%
“…Patients under the age of 30 represented 84.6% of our study population. In Burkina-Faso in 2010, Bonane-Thieba et al found an average age of 24.1 years with 78.8% of cases being less than 30 years old [4]. These data support the hypothesis according to which youth is the target of breast tumors.…”
Section: Agementioning
confidence: 72%
See 2 more Smart Citations
“…Male breast pathology is rare in Burkina Faso [7]. Some studies have been carried out on the epidemiological, histopathological and therapeutic aspects of malignant lesions among men [10].…”
Section: Introductionmentioning
confidence: 99%